2021
DOI: 10.1021/acsbiomedchemau.1c00031
|View full text |Cite
|
Sign up to set email alerts
|

Binding of AP Endonuclease-1 to G-Quadruplex DNA Depends on the N-Terminal Domain, Mg2+, and Ionic Strength

Abstract: The base excision repair enzyme apurinic/apyrimidinic endonuclease-1 (APE1) is also engaged in transcriptional regulation. APE1 can function in both pathways when the protein binds to a promoter G-quadruplex (G4) bearing an abasic site (modeled with tetrahydrofuran, F) that leads to enzymatic stalling on the noncanonical fold to recruit activating transcription factors. Biochemical and biophysical studies to address APE1’s binding and catalytic activity with the vascular endothelial growth factor (VEGF) promot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(90 citation statements)
references
References 78 publications
15
75
0
Order By: Relevance
“…To observe the effect of the multivalent cation presence in APE1 binding, the assays were repeated in the presence of 10 mM Sm 3+ as a substitute for Mg 2+ with the purpose of preventing any catalytic activity on the substrates but not to impact effects on the binding . Our prior work found the binding between catalytically inactivated APE1 and a G4 was Mg 2+ -dependent . Therefore, the discussion here will focus on the Sm 3+ studies, but for completeness of the study, binding without Mg 2+ was analyzed and is provided in Figure S10.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…To observe the effect of the multivalent cation presence in APE1 binding, the assays were repeated in the presence of 10 mM Sm 3+ as a substitute for Mg 2+ with the purpose of preventing any catalytic activity on the substrates but not to impact effects on the binding . Our prior work found the binding between catalytically inactivated APE1 and a G4 was Mg 2+ -dependent . Therefore, the discussion here will focus on the Sm 3+ studies, but for completeness of the study, binding without Mg 2+ was analyzed and is provided in Figure S10.…”
Section: Resultssupporting
confidence: 85%
“…To understand the role of cysteine oxidation to sulfenic acids in APE1 in influencing DNA binding, fluorescence anisotropy binding assays were conducted following a method previously reported . The binding studies were conducted using the sequences shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AP site and BER machinery destabilize the normal double helix structure and lower the energy barrier for forming G-quadruplexes in some sequences [ 31 ]. The AP endonuclease of Ape1 is highly attenuated at abasic sites in certain parts of a G-quadruplex structure, compared with its activity on double-strand DNA [ 32 ]. In such cases, rather than incising the phosphodiester bond, Ape1 now helps stabilize these G-quadruplexes.…”
Section: Ape1 Overviewmentioning
confidence: 99%
“…Fluorophores attached to DNA or RNA oligomers have enabled monitoring their migration during gel electrophoresis experiments [1] and the tracking of these polymers in single-molecule experiments. [2,3] Additionally, the binding interactions between DNA or RNA with other nucleic acids, [4] proteins, [5] or ligands, [6] as well as in sequencing-by-synthesis experiments, can be followed. [7] There exist many fluorophores tailored for various applications in which fluorescein, rhodamine, BODIPY, and cyanine3 (Cy3) or variants thereof are used with some frequency in nucleic acid visualization (Figure 1).…”
Section: Introductionmentioning
confidence: 99%